The development of e-construction (green building) with geographic information system - Tajul Baharuddin, Mohamad Faizal; Sarif, Abdul Sukor; Lim, Michael Gibson (Penerbit UTHM, 2020)
Building has impacted to our environment and nearly 40% of natural resource were extracted due to construct infrastructures [1]. Conventional building consumes nearly 70% of electricity and nearly 38% percent of CO2 produced [2]. Green Building (GB) comes in place to create a new building philosophy and encourage to contribute a more environmentally friendly material. Furthermore, the implementation of green building can be enabled a building to perform a more efficient and more environment in terms of energy and water reduction..